2007
DOI: 10.1103/physrevc.76.054308
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phonon excitations inCd114with the(n,n'

Abstract: Properties of low-spin states in 114 Cd have been studied with the (n, n γ ) reaction. Gamma-ray angular distributions and excitation functions have been used to characterize the decays of the excited levels. Level lifetimes have been obtained with the Doppler-shift attenuation method. Sixteen new levels and many new transitions have been suggested below 3.5 MeV in excitation energy. Levels belonging to the phonon multiplets have been proposed based on their decay patterns and collectivity, and the existing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
(125 reference statements)
3
19
0
Order By: Relevance
“…In fact, it was noted [9] that the IBM-2 calculations only agreed with the data for the three-phonon levels that were yrast, whereas the nonyrast levels had serious disagreements. Similar results have now been observed for 114 Cd [31]. In the present work, the detailed spectroscopic data on low-spin levels available for a series of stable Cd isotopes are examined for the appearance of systematic deviations from expected vibrational patterns.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In fact, it was noted [9] that the IBM-2 calculations only agreed with the data for the three-phonon levels that were yrast, whereas the nonyrast levels had serious disagreements. Similar results have now been observed for 114 Cd [31]. In the present work, the detailed spectroscopic data on low-spin levels available for a series of stable Cd isotopes are examined for the appearance of systematic deviations from expected vibrational patterns.…”
Section: Introductionsupporting
confidence: 77%
“…[9,31] and will only be briefly outlined here for completeness. In both nuclei, the observed B(E2; 0 + 3 → 2 + 2 ) values are a factor of 2 greater than calculated, whereas the observed B(E2; 2 + 2 → 2 + 1 ) values are a factor of 2 smaller than predicted.…”
Section: Discussion Of Two-phonon Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…These refined peak parameters were used to establish the radiative neutron-capture decay-scheme of 114 Cd. Data from experimental papers and recent compilations [7][8][9][10] were used in the decay scheme construction. The unsuppressed spectrum was unfolded with the methodology described in detail in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [11][12][13][14][15], using both the (n, n ′ γ) reaction and radioactive decay, have begun to characterize the higher-lying states, especially candidate states for the three-phonon multiplet in 112,114,116 Cd. These studies have revealed consistent discrepancies between the IBM-2 model calculations, which incorporate strong mixing, and the experimental data [11,16].…”
mentioning
confidence: 99%